Population pharmacokinetics of farletuzumab, a humanized monoclonal antibody against folate receptor alpha, in epithelial ovarian cancer - Farrell, Colm (Springer-Verlag, 2012)
PURPOSE: The purpose of this analysis was to develop a population pharmacokinetic model for farletuzumab, a humanized immunoglobulin (Ig)G(1) monoclonal antibody (mAb) to the folate receptor alpha, which is a receptor over-expressed in ovarian cancer, but largely absent from normal tissue. METHODS: In total, 2,472 samples were included in the building of the pharmacokinetic model. Farletuzumab 12.5–400 mg/m(2) had been administered via intravenous infusion to 79 patients with advanced ovarian cancer enrolled in one of the two clinical studies. Data were analyzed by a nonlinear mixed-effects modeling approach. RESULTS: Farletuzumab pharmacokinetics was best described by a two-compartment model with first-order (linear) elimination. In the final model, estimated values of clearance and volume of distribution of the central compartment were 0.00784 l/h and 3.00 l, respectively. Body weight was the only covariate investigated that explained inter-patient variability in clearance and the central volume of distribution. There was no effect of age, human anti-human antibodies, or concomitant chemotherapy on the pharmacokinetics of farletuzumab. Simulations showed that, when the mg/kg/week dose was maintained, steady-state exposure to farletuzumab was similar with dosing every week or every 3 weeks. CONCLUSIONS: The pharmacokinetic parameters of farletuzumab are similar to those of other IgG mAbs. The results support weight-based dosing of farletuzumab on a weekly or 3-weekly schedule.